2015
DOI: 10.2337/db14-1870
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Insulin Secretory Capacity and Weight Loss Are the Predominant Predictors of Glycemic Control in Patients With Type 2 Diabetes Randomized to Roux-en-Y Gastric Bypass

Abstract: Improvement in type 2 diabetes after Roux-en-Y gastric bypass (RYGB) has been attributed partly to weight loss, but mechanisms beyond weight loss remain unclear. We performed an ancillary study to the Diabetes Surgery Study to assess changes in incretins, insulin sensitivity, and secretion 1 year after randomization to lifestyle modification and intensive medical management (LS/IMM) alone (n = 34) or in conjunction with RYGB (n = 34). The RYGB group lost more weight and had greater improvement in HbA1c. Fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 27 publications
3
41
0
Order By: Relevance
“…Similar findings have been reported for RYGB [35, 36]. Another study demonstrated an early attenuation of the glucagon response to a mixed meal early after both LSG and RYGB, but fasting glucagon levels were similar to preoperative values at 1 year after either operation type [13].…”
Section: Discussionsupporting
confidence: 78%
“…Similar findings have been reported for RYGB [35, 36]. Another study demonstrated an early attenuation of the glucagon response to a mixed meal early after both LSG and RYGB, but fasting glucagon levels were similar to preoperative values at 1 year after either operation type [13].…”
Section: Discussionsupporting
confidence: 78%
“…The hyperinsulinaemia that accompanies rapid rates of prandial glucose appearance and clearance in GB patients has been taken as evidence that surgery enhances β‐cell function. In fact, previous studies implicate increased incretin stimulation, as well as greater β‐cell glucose responsiveness after eating, to explain higher rates of insulin secretion. The findings presented here support a dramatically different model of surgical effects on insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, GB increases the incretin effect in both diabetic and non‐diabetic individuals, and the effect of GLP‐1 to stimulate insulin release increases more than 2‐fold . Modelling of plasma C‐peptide concentrations in GB subjects after meals also suggests increased β‐cell sensitivity to glucose . However, the complexity of insulinotropic stimuli in surgical patients makes attribution of factors controlling insulin secretion difficult.…”
Section: Introductionmentioning
confidence: 99%
“…However, T2D is a progressive disease associated with increased risk for CVD and microvascular complications. Furthermore, evidence shows that metabolic improvement following surgery in patients with T2D correlates with shorter diabetes duration at baseline, possibly reflecting more preserved b-cell function (19,52,96). This suggests that unnecessarily delaying access to surgery might reduce health benefits and cost-effectiveness of surgery in patients with diabetes.…”
Section: Metabolic Surgery Versus Traditional Bariatric Surgerymentioning
confidence: 99%